2021
DOI: 10.1002/star.202100092
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Assisted Extraction of Lychee (Litchi chinensis Sonn.) Seed Starch: Physicochemical and Functional Properties

Abstract: High-power ultrasound (HPU) is a non-thermal processing method that has been researched and used in the last years. The application of ultrasound can modify and improve some technologically important compounds such as starch. This research aimed to examine the effect of ultrasound treatment on yield, physicochemical, and functional properties of lychee seed starch (LS). HPU experimental conditions used were sonication time (5 and 20 min) and amplitude (40% and 70% ). Starch yield significantly increased with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…[ 44,45 ] It was reported that the cavitation can break intermolecular bonds of starch and decrease its yield. [ 46 ] However, Morales‐Trejo et al showed the ultrasonic treatment (alkaline extraction method + ultrasonic in 40% and 70% amplitude in 5 and 20 min) significantly increased the Lychee starch yield and by increasing amplitude and time the yield was also increased [ 17 ] due to the mechanical action of sonication which led to cell wall disruption. [ 47 ]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 44,45 ] It was reported that the cavitation can break intermolecular bonds of starch and decrease its yield. [ 46 ] However, Morales‐Trejo et al showed the ultrasonic treatment (alkaline extraction method + ultrasonic in 40% and 70% amplitude in 5 and 20 min) significantly increased the Lychee starch yield and by increasing amplitude and time the yield was also increased [ 17 ] due to the mechanical action of sonication which led to cell wall disruption. [ 47 ]…”
Section: Resultsmentioning
confidence: 99%
“…The amylose content affects the technological and functional properties of starch including gelatinization, recrystallization (retrogradation), solubilization, swelling, viscosity and texture, and the formation features. [ 17 ] The amylose content of starch samples isolated by various methods is shown in Figure 1B. The range of amylose content was between 17.7% (LAE‐C) and 18.13% (EAE‐A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations